Le savoir des communautés de hackers. Le digital comme objet de passion, domaine de niche et vision avant-gardiste - Lisa Bolz (Communication)
The Chaos Computer Club (CCC) is a German hacker community founded in 1981 and known for its promotion of activism and its activities that skirt the edge of legality. Today it has become an institution the German Bundestag sometimes turns to for help. Drawing on the as-yet untapped corpus of the magazine Datenschleuder, an old media (see Magaudda and Balbi for this terminology) taken up by a new generation of hackers, the article offers an analysis of how CCC sees itself, especially in its first phase, by explicitly emphasizing its non-deterministic conception of digital transformations. The analysis demonstrates that this community of “good hackers” is helping to expose malfunctions and combat certain forms of cybercrime, which, in Germany has largely led to the development of hacking rules and standards, activism for freedom of information, and public education about information technology.